2017
DOI: 10.1111/nph.14789
|View full text |Cite
|
Sign up to set email alerts
|

The roles of AaMIXTA1 in regulating the initiation of glandular trichomes and cuticle biosynthesis in Artemisia annua

Abstract: SummaryThe glandular secretory trichomes (GSTs) on Artemisia annua leaves have the capacity to secrete and store artemisinin, a compound which is the most effective treatment for uncomplicated malaria. An effective strategy to improve artemisinin content is therefore to increase the density of GSTs in A. annua. However, the formation mechanism of GSTs remains poorly understood.To explore the mechanisms of GST initiation in A. annua, we screened myeloblastosis (MYB) transcription factor genes from a GST transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
122
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 130 publications
(124 citation statements)
references
References 85 publications
0
122
0
Order By: Relevance
“…A). These tissues have abundant glandular trichomes, which are closely related with artemisinin biosynthesis . Additionally, AaADS showed high expression in the shoot, bud, and leaf, but low expression in the root, stem, and flower (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A). These tissues have abundant glandular trichomes, which are closely related with artemisinin biosynthesis . Additionally, AaADS showed high expression in the shoot, bud, and leaf, but low expression in the root, stem, and flower (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Artemisinin‐based combination therapies have been proposed by the World Health Organization as the best treatment for malaria . Artemisinin is produced in glandular secretory trichomes, which are mainly distributed in young leaves and buds of A. annua . The biosynthetic pathway of artemisinin has been almost completely elucidated in recent years .…”
Section: Introductionmentioning
confidence: 99%
“…In order to further investigate AaHD8 functions, we screened the cDNA library of A. annua young leaves for proteins interacting with AaHD8. Several proteins were identified, including a MYB transcription factor AaMIXTA1 which has been proven to be involved in regulating glandular trichome initiation and cuticle biosynthesis in A. annua by our group (Shi et al ., ). In further Y2H assays, AaHD8 strongly interacted with AaMIXTA1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Artemisia annua is well‐known for producing the antimalarial drug artemisinin, specifically synthesized in glandular trichomes, which makes it a suitable candidate plant for investigating the molecular mechanism of glandular trichome development (Graham et al ., ; Yan et al ., ). Previously, we demonstrated that the HD‐ZIP IV transcription factor AaHD1 and the MIXTA‐like protein AaMIXTA1 played important roles in promoting glandular trichome initiation in A. annua (Shi et al ., ; Yan et al ., ). AaMIXTA1 was identified to be a positive regulator of cuticle biosynthesis (Shi et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation